Rozporządzenia językowe Józefa II dla Galicji (1780–1790) - Timofejew, Dmitrij (Postscriptum Polonistyczne, 2020)
The article aims at analysing selected legal acts concerning language policy issued by Joseph II for Galicia in the period of time between 1780 and 1790. The consequences of these acts are also described. For the Austrian authorities, Galicia – as a multilingual and multicultural region – was a challenge because there had not been any strong state authority or bureaucratic structure there even before Galicia became a part of the Habsburg monarchy. One of the biggest problems for the local officials was a very limited knowledge of the German language amongst the inhabitants of the region, therefore a number of legal actions had to be initiated to enforce the local people’s learning of the official language of the Habsburg monarchy, and yet, at the same time the languages of minorities were recognized.